Cross border railway trade and urban development in minority ethnic autonomous regions: causal analysis with double machine learning - Chang Gao; Lianjun Yao; Xueyuan Wang (Cogent Economics & Finance)
The system of regional ethnic autonomy has endowed ethnic minority areas with greater autonomy in economic and social development, and exploring their regional economic development has a unique significance. This study used panel data from 120 ethnic autonomous counties in China from 2005 to 2021 to construct a double machine learning model to empirically test the impact of cross-border railway trade on urban development in ethnic autonomous counties and its mechanism of action. The results show: (1) Cross-border railway trade can significantly promote urban development in ethnically autonomous counties. Each unit increase can promote the urban development of ethnically autonomous counties by 35%. (2) The cross-border railway trade promotes urban development through three pathways: financial development, knowledge spillover, and industrial upgrading. (3) Cross-border railway trade has a better urban development effect on the ‘intermixed living on a large scale’ autonomous counties than the ‘concentrated settlement on a smaller scale’ autonomous counties; and it has a more significant urban development effect on the autonomous counties located in the western transportation corridor and benefited by the policy. The conclusions provide useful policy implications for economic development in regions with concentrated ethnic minorities.